2019
DOI: 10.1111/cas.14171
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐derived xenograft models of non‐small cell lung cancer for evaluating targeted drug sensitivity and resistance

Abstract: Patient‐derived xenograft (PDX) models are a useful tool in cancer biology research. However, the number of lung cancer PDX is limited. In the present study, we successfully established 10 PDX, including three adenocarcinoma (AD), six squamous cell carcinoma (SQ) and one large cell carcinoma (LA), from 30 patients with non‐small cell lung cancer (NSCLC) (18 AD, 10 SQ, and 2 LA), mainly in SCID hairless outbred (SHO) mice (Crlj:SHO‐PrkdcscidHrhr). Histology of SQ, advanced clinical stage (III‐IV), status of lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
(76 reference statements)
0
26
0
Order By: Relevance
“…7c). We established two PDXs from patients with EGFR mutations 19 . PDX LC#7 had EGFR-L858R and a discernible level of AXL, lacking phosphorylated IGF-1R.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7c). We established two PDXs from patients with EGFR mutations 19 . PDX LC#7 had EGFR-L858R and a discernible level of AXL, lacking phosphorylated IGF-1R.…”
Section: Resultsmentioning
confidence: 99%
“…Patient tumor samples were obtained with informed consent. Surgically resected tumor specimens were divided into small pieces (3-5 mm) and implanted into the subcutaneous flank tissue of SHO mice 19 . The PDX LC#7 was from an 81-year-old Japanese male (pT2N2M0, stage IIIA) with lung adenocarcinoma containing EGFR-L858R.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to tumor type, other factors, such as the degree of mouse immunodeficiency (i.e., which immunocompromised strain is used) and size of the grafted specimen could also be important factors. Regarding NSCLC, PDXs have been extensively used in preclinical studies targeting mostly EGFR [ 4 , 7 , 8 ]. Interestingly, published studies have reported a higher grafting efficiency for lung squamous cell carcinomas (LUSC) in comparison to lung adenocarcinomas (LUAD) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A common observation is the high histological resemblance between the primary tumor and early passage mouse xenografts [ 4 , 7 , 9 , 12 , 13 ]. More recent reports have focused on the comparison of the molecular characteristics of primary tumors and the respective mouse counterparts.…”
Section: Introductionmentioning
confidence: 99%